Contract killings: a crime script analysis - de Korte, Laura R. (Trends in organized crime, 2022)
This article contributes to our existing knowledge through a crime script analysis of contract killings, based on six extensively analyzed police investigations in the Netherlands. Starting from a universal crime script, a more specific crime script for contract killings is elaborated. To provide a clear picture of the whole process, the description of the scenes focuses on requirements, facilitators, modi operandi, and preparatory actions. A comparison of liquidation investigations is made through a crime script analysis, which results in three types of requirements: vehicles, automatic weapons, and technical equipment, including PGP-telephones and beacons. In addition, spy shops turn out to play a major role in liquidations as facilitators. Due to a lack of licensing and regulations, the owners of spy shops can decide to a large extent on their own procedures. This leads to the possibility of buying and selling equipment anonymously and with large amounts of cash, which facilitates the preparation of liquidations and crime in general. Hitmen are the second type of important facilitators. The analysis reveals that all liquidation investigations contain indications of a principal to whom account has to be held. Two investigations clearly demonstrate financial rewards for contract killings.